One Global Family: Insights from Confucian Tenets and Practices - Guo, Yiwen (Journal of Dharma, 2025)
This article investigates the relevance and application of Confucianism in today’s globalized society, emphasizing its influence on individual, familial, social, and global dynamics. It explores Confucian philosophy as a comprehensive framework for addressing various aspects of life, including management and organizational practices, both in East Asia and internationally. The study also addresses the challenges, critiques, adaptations, and innovations within Confucianism, comparing it with Western philosophies to reveal opportunities for coexistence and social development in a pluralistic world. Finally, the article traces the evolution of Confucianism, from Confucius’ progressive vision to its integration with other traditions, culminating in its emergence as a global philosophy that promotes the idea of a united world family.